2014
DOI: 10.7762/cnr.2014.3.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fat Intake, Body Fat Composition and Intra-Abdominal Fat after Bariatric Surgery

Abstract: Bariatric surgery is considered to be the effective treatment alternative conducted over the lifetime for reducing weight in patients with clinically morbid obesity. For many patients, the benefits of weight loss, including decreases in blood glucose, lipids, and blood pressure as well as increase in mobility, will outweigh the risks of surgical complications. But patients undergoing bariatric surgery have the least risk for long-term diet-related complications as reported in several studies. Thus, with an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A study by Verger et al [58] showed that the insufficient intake of PUFA in the energy value of the diet was noted in RYGB patients, while in SG patients, it was similar to the one in the present study. Lim et al [68] emphasized favorable changes that occurred in the nutrition of a 51-year-old patient 6 months post-LSG (SAFA intake reduction, the increased intake of MUFA and PUFA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Verger et al [58] showed that the insufficient intake of PUFA in the energy value of the diet was noted in RYGB patients, while in SG patients, it was similar to the one in the present study. Lim et al [68] emphasized favorable changes that occurred in the nutrition of a 51-year-old patient 6 months post-LSG (SAFA intake reduction, the increased intake of MUFA and PUFA).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed a significant reduction in dietary cholesterol intake, which exceeded the reference values by over 2-fold before surgery and was within normal limits 12 months after surgery. Other authors also emphasized a considerable decrease in cholesterol consumption [17,68]. The intake of cholesterol should be limited mainly in individuals with its high levels in the plasma [35].…”
Section: Discussionmentioning
confidence: 99%